Validity Feasibility of Interactive Media Based on Wordwall Game in Learning Pancasila Education Class IV Elementary School - Chairunnisa, Azizah; Reinita, Reinita; Putera, Rafhi Febryan; Mansurdin, Mansurdin (FKIP - Universitas Riau, 2025)
This study is motivated by the suboptimal utilization of technology-based learning media in elementary schools. Classroom learning still largely relies on traditional media such as textbooks, blackboards, and illustrations. The purpose of this research is to develop an interactive, game-based learning medium using Wordwall for Pancasila Education among fourth-grade students at SDN Daerah I Pauh, Padang City. The research applies a Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through questionnaires that had been validated by subject matter experts, media experts, and language experts. The validity assessment results are as follows: the content expert gave a score of 83.3%, categorized as “valid”; the media expert gave a score of 95%, categorized as “very valid”; and the language expert gave a score of 81.25%, also categorized as “valid.” The overall validity score, based on the average percentage, was 86.56%, which falls into the “very valid” category. These findings indicate that the Wordwall-based interactive game medium is highly valid for supporting Pancasila Education learning in elementary schools.